Immobilization of Low-Cost Alternative Vegetable Peroxidase (Raphanus sativus L. peroxidase): Choice of Support/Technique and Characterization - Gabrielle Souza da Silva Barbosa; Maria Emanuela P. S. Oliveira; Ana Beatriz S. dos Santos; Osmar Calderón Sánchez; Cleide Mara Faria Soares; Alini Tinoco Fricks (Molecules, 2020)
In the present work the radish (Raphanus sativus L.) was used as the low-cost alternative source of peroxidase. The enzyme was immobilized in different supports: coconut fiber (CF), calcium alginate microspheres (CAMs) and silica SBA-15/albumin hybrid (HB). Physical adsorption (PA) and covalent binding (CB) as immobilization techniques were evaluated. Immobilized biocatalysts (IBs) obtained were physicochemical and morphologically characterized by SEM, FTIR and TGA. Also, optimum pH/temperature and operational stability were determined. For all supports, the immobilization by covalent binding provided the higher immobilization efficiencies—immobilization yield (IY%) of 89.99 ± 0.38% and 77.74 ± 0.42% for HB and CF, respectively. For CAMs the activity recovery (AR) was of 11.83 ± 0.68%. All IBs showed optimum pH at 6.0. Regarding optimum temperature of the biocatalysts, HB-CB and CAM-CB maintained the original optimum temperature of the free enzyme (40 °C). HB-CB showed higher operational stability, maintaining around 65% of the initial activity after four consecutive cycles. SEM, FTIR and TGA results suggest the enzyme presence on the IBs. Radish peroxidase immobilized on HB support by covalent binding is promising in future biotechnological applications.